Avaliação dos conhecimentos e práticas de profissionais de saúde sobre a dor do recém-nascido - Marques, Ana Claudia Garcia (2016)
Introduction: With the advancement of technological and scientific development, there is an increasing use of invasive and intensive treatment life support of sick newborns, but such assistance can lead to painful stimuli causing suffering to them. The necessary tools for detection of painful suffering are still underestimated, but currently there is a growing interest in the proper management of neonatal pain. Objective: This study aims to assess knowledge and practices of health professionals working in a neonatal unit on newborn pain. Methodology: This is a descriptive and analytical survey with a qualitative exploratory approach held in a referral hospital in neonatal care in a Northeastern capital. Analysis of the interviews was carried out through thematic analysis, which is one of the four types of content analysis. We conducted 36 interviews with professionals who work in Neonatal Intensive Care Unit and Intermediate Care Unit in direct care of newborns, including physicians, nurses, physiotherapists, speech therapists and occupational therapists. Results: The data showed that the interviewed professionals recognize that neonatal pain has been historically neglected and now scientific evidence shows their existence. Thus the explanations and interpretations attributed by professionals show some aspects whose categories are objects of analysis in this study: The pain exists, leaves sequels and marks and traumatizes; Expressions of pain are perceived, but not enough; Pain was and still is very neglected. From the reports, we identified lack of information during academic formation handicapping the application of knowledge in practice. This is evident both in perception and professional intervention. Conclusion: The results obtained in this study demonstrated that professionals working in the Neonatal Unit have knowledge on newborn pain, despite certain limitations, and many of them perceive its signals. Thus, the challenge is not understanding and perception of pain, but acting on it.